Catalytic Friedel–Crafts/Lactonization Domino Reaction: Facile Access to 3‐Hydroxybenzofuran‐2‐one Scaffold. Issue 9 (17th January 2014) - Vetica, Fabrizio; Pelosi, Alessandra; Gambacorta, Augusto; Loreto, M. Antonietta; Miceli, Martina; Gasperi, Tecla
Abstract: A valuable Lewis‐acid‐catalysed domino reaction involving a Friedel–Crafts alkylation of variously substituted phenols followed by a direct lactonization has been successfully developed (22 examples, yields up to 98 %). This protocol tolerates not only opposite electron demand substituents on the starting materials, but also drastic modifications of the alkylating agents, and gives direct access to the corresponding 3‐hydroxy‐benzofuran‐2‐ones, which could easily undergo further chemical transformation. The relevance of our method was further confirmed by the straightforward synthesis of rac ‐BHFF, the recently discovered and extremely promising positive allosteric modulator of the GABAB receptor. Abstract : 3‐Hydroxybenzofuran‐2‐one derivatives are easily obtained by a Friedel–Crafts/lactonization domino reaction starting from phenols and alkylating agents bearing an opposite electron demand substituents. The use of TiCl4 as catalyst (10 mol‐%) under mild reaction conditions smoothly gives the desired products in high yields (22 examples, up to 98 %).